Internalization of Islamic Educational Values and Character Strengthening for Children of Indonesian Migrant Workers at The at-Tanzil Learning Center in Lembah Jaya, Malaysia - Badruddin; Sa'adah; Nur Fazilah Bugis (CV. Era Digital Nusantara, 2025)
This study examines the process of internalizing Islamic educational values and strengthening character for children of Indonesian Migrant Workers (PMI) at the At-Tanzil Lembah Jaya Learning Center (SB), Ampang, Selangor, Malaysia. PMI children face structural exclusion from the formal education system due to their parents' illegal immigration status. This study describes the effectiveness of five program pillars: worship practices, tahsin-tajwid, tartil Al-Qur'an, aqidah akhlak, and batik art. The approach used is descriptive qualitative based on participatory observation. The results show that consistent habituation of worship routines can shape the discipline and emotional stability of students. The nagham bayati and nahawand methods have been proven to increase Quranic literacy and self-confidence of students. Social programs such as visits to orphanages instill the values of empathy and Islamic brotherhood. The integration of Islamic and national identities through flag ceremonies and batik art strengthens the identity of diaspora children. Overall, the community-based non-formal Islamic education model at SB At-Tanzil has succeeded in becoming a concrete response to the failure of the formal system in serving migrant children and has proven that the depth of educator commitment, the relevance of the contextual approach, and community solidarity are key factors for success.